Pengaruh Profitabilitas, Dividend Payout Ratio dan Inflasi Terhadap Harga Saham: (Effect of Profitability, Dividend Payout Ratio and Inflation on Stock Prices) - Herman Setiawan; Victoria Victoria; Karen Victoria; Holfian Daulat Tambun Saribu; Erika Erika (UPT Penerbitan Universitas Jember, 2021)
The presence of the capital market in Indonesia is marked by the number of investors who purchase shares of entities that are registered in the capital market. The purpose of this research is to examine and analyze the effect of profitability, dividend payout ratio and inflation on share prices in consumer goods entities listed on the Indonesia Stock Exchange in 2014-2018. This type of research is quantitative. The population of this study is 41 consumer goods companies listed on the Indonesia Stock Exchange for the period 2014- 2018, the sample of this study is 17 companies x 5 years = 85 samples. The data analysis method of this research is to use multiple linear regression with SPSS. The results of this study are Profitability has a significant and significant effect on stock prices, while Dividend Payout Ratio and inflation have no effect on Stock Prices, and simultaneously Profitability, Dividend Payout Ratio and inflation have a significant and significant effect on Share Prices in Consumer Goods Entities listed on the Indonesia Stock Exchange. 2014-2018.